IL‐12 and IL‐4 activate a CD39‐dependent intrinsic peripheral tolerance mechanism in CD8+ T cells. Issue 6 (8th April 2016) - Noble, Alistair; Mehta, Hema; Lovell, Andrew; Papaioannou, Eleftheria; Fairbanks, Lynette
Abstract : CD8 regulatory T cells are induced by differentiation with IL‐4 and IL‐12. This process involves upregulation of CD39, an ecto‐nucleotidase involved in regulatory function via ATP breakdown. In vivo tolerance models are associated with expression of CD39 on CD8 T cells, suggesting both cytokine and nucleotide environments control CTL expansion. Abstract : Immune responses to protein antigens involve CD4 + and CD8 + T cells, which follow distinct programs of differentiation. Naïve CD8 T cells rapidly develop cytotoxic T‐cell (CTL) activity after T‐cell receptor stimulation, and we have previously shown that this is accompanied by suppressive activity in the presence of specific cytokines, i.e. IL‐12 and IL‐4. Cytokine‐induced CD8 + regulatory T (Treg) cells are one of several Treg‐cell phenotypes and are Foxp3 − IL‐10 + with contact‐dependent suppressive capacity. Here, we show they also express high level CD39, an ecto‐nucleotidase that degrades extracellular ATP, and this contributes to their suppressive activity. CD39 expression was found to be upregulated on CD8 + T cells during peripheral tolerance induction in vivo, accompanied by release of IL‐12 and IL‐10. CD39 was also upregulated during respiratory tolerance induction to inhaled allergen and on tumor‐infiltrating CD8 + T cells. Production of IL‐10 and expression of CD39 by CD8 + T cells was independently regulated, being respectively blocked by extracellular ATP and enhanced by an A2A adenosine receptor agonist. Our results suggest that any CTL can develop suppressive activity when exposed to specific cytokines in the absence of alarmins. Thus negative feedback controls CTL expansion under regulation from both nucleotide and cytokine environment within tissues.